Pengaruh Kualitas Produk, Brand Image dan Brand Awareness terhadap Keputusan Pembelian Sepatu Dr. Martens (Studi pada Konsumen Sepatu Dr. Martens di Jakarta) - Muhamad Reza Adhiwira; Rina Ayu Vildayanti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The footwear industry has experienced significant growth, particularly in the fashion segment, where shoes are no longer considered solely as functional items but also as lifestyle products that reflect personal identity and social expression. Among various global brands, Dr. Martens has become one of the premium footwear products with a distinctive image and loyal consumer base. This study aims to examine the influence of Product Quality, Brand Image, and Brand Awareness on Purchasing Decisions of Dr. Martens shoes in Jakarta. The research employed a quantitative method with non-probability sampling, using the accidental sampling technique. The population consisted of consumers who had purchased Dr. Martens shoes, and a total of 100 respondents were collected through questionnaires distributed among university students. The instrument used was a Likert scale questionnaire, and the data were analyzed using multiple linear regression with SPSS version 22. The findings show that Product Quality and Brand Awareness have a positive and significant influence on Purchasing Decisions, while Brand Image does not show a significant effect. These results indicate that consumers are more influenced by tangible product attributes and the level of brand recognition than by brand perception alone. This highlights the importance for premium footwear companies to maintain consistent product quality and strengthen brand awareness strategies, especially through digital marketing channels, to influence purchase behavior. The study contributes to the literature on consumer behavior and provides practical insights for fashion industry players to formulate effective marketing strategies in a competitive market.